Bioinspired, Ultra‐Fast Polymerization of Dopamine under Mild Conditions. Issue 23 (2nd August 2022) - Zhou, Xiaoman; Gao, Sijia; Huang, Di; Lu, Zhengbo; Guan, Ying; Zou, Lei; Hu, Keling; Zhao, Zhuo; Zhang, Yongjun
Abstract: Spontaneous oxidative polymerization of dopamine (DA) is widely exploited as a facile and versatile method for surface modification. However, the reaction is very slow and only occurs in alkaline solutions, which severely limit its applications. Herein it is reported that the reaction can be dramatically accelerated by using Fe 2+ as catalyst. While it takes hours and days using conventional method, the Fe 2+ ‐catalyzed reaction finishes almost immediately at pH 7.0. In addition, under the catalysis of Fe 2+, the reaction can occur at a pH down to 4.0. The fast Fe 2+ ‐catalyzed polymerization of DA leads to fast deposition of polydopamine (PDA) coating, thus allowing fast surface modification and textile dyeing. The Fe 2+ ‐catalyzed reaction also allows spatial control over the PDA deposition. The fast, simple, and mild surface modification method developed here will find applications in numerous fields. Abstract : Surface modification via spontaneous oxidative polymerization of dopamine is now widely exploited for its simplicity and mildness, however, the slow reaction and an alkaline environment severely limit its applications. Herein it is reported that the reaction can be dramatically accelerated by using Fe 2+ as catalyst even at neutral pH, thus allowing fast surface modification under mild conditions.